1977
DOI: 10.1159/000114808
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Cells in the Cerebrospinal Fluid

Abstract: Comparative ultrastructural findings of meninges, ventricular ependyma and choroid plexus of mammals including man were summarized with the aim of a better understanding as to which cells can play a role as macrophages in the cerebrospinal fluid (CSF) cytology. Differences between phagocytic capacity of pial cells and arachnoid cells were emphasized. Comparative investigations showed that most of the cells in the CSF originate from the blood. Scanning electron microscopy of the subarachnoid space and cytologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

1979
1979
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 7 publications
1
8
0
1
Order By: Relevance
“…Studies of immunoglobulin containing cells in CSF have been performed by Guseo (1974) and Dayan and Stokes (1973). Guseo examined 3 cases of lymphocytic meningitis and reported that plasma cells, immature plasma cells and large transformed cells have positive fluorescence.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of immunoglobulin containing cells in CSF have been performed by Guseo (1974) and Dayan and Stokes (1973). Guseo examined 3 cases of lymphocytic meningitis and reported that plasma cells, immature plasma cells and large transformed cells have positive fluorescence.…”
Section: Discussionmentioning
confidence: 99%
“…Ele define uma condição normal ou patológica através da análise da sinalização 6 . No entanto, ao contrário do que a maioria dos autores tem referido 1,2,4,6,7,0,1^ 0 nosso grupo controle apresentou figuras nítidas de sinalização, com a presença de linfócitos ativados, mitoses típicas, figuras de peripolese e emperipolese e reticulomonócitos modificados.…”
Section: Comentáriosunclassified
“…There are some report's describing that the endolymphatic sac (ES) has some floating cells in its lumen [3,7,13]; and those cells somewhat resemble the one appearing in the subarachnoid space [5,11], The heterogenous foreign bodies injected into the endolymph of experimental animals via the various path ways were accumulated in the free-floating cells (FFC) and in the epithelial lining of the ES [1,4,7], Therefore, it has been thought that the ES has a reactive and defensive role against the foreign body in the endolymph. The morphology of these FFC were pre viously described by Guild [3], and recently Rask-Andersen and Stahle [ 13] further dis cussed about the lymphocyte-macrophage in teraction in the ES.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, it has been known that the ce rebrospinal fluid (CSF) cells change the num ber and the own structures under the various pathological conditions [11], and they play a defensive role against central nervous system (CNS) diseases [5,11]. Accordingly, FFC in the ES could be considered to have a similar defense mechanism against the inner ear dis ease.…”
Section: Introductionmentioning
confidence: 99%